Risk analysis of the mortality from the diseases of the circulatory system in the Ural cohort of emergency-irradiated population for the years 1950–2015 - L. Yu. Krestinina; S. S. Silkin; M. O. Degteva; A. V. Akleyev (Радиационная гигиена)
The paper describes for the first time the results of the radiation effect study using the example of the analysis of circulatory system disease mortality in newly established cohort combining the population exposed in 1950–1960 due to 2 radiation incidents in the Southern Urals (the Techa River and East-Urals radioactive Trace). The cohort consists of 60,205 people. Over a 65-year follow up period 14,830 deaths from all diseases of the circulatory system were registered. Out of this number 6,163 deaths were from ischemic heart disease, and 4,388 deaths were from cerebrovascular diseases. Analysis was performed on the basis of individualized estimates of dose accumulated in muscle tissue (both internal and external components of the dose), calculated with new Techa River Dosimetry System 2016. As per the latest calculations, mean dose to muscle tissue in members of the combined cohort was 34 mGy, maximum dose was 995 mGy. Simple parametric model of excess relative risk (ERR) was used in the analysis. The number of person-years at risk was 1836,203. The findings of the analysis show linear increase of mortality risk per unit dose from all the disease of circulatory system (ERR/100 mGy was 3%; 95% CI: 0,8%; 5,2%) and from ischemic heart disease (ERR/100 mGy was 9,2%; 95% CI: 5,4%; 13,5%). with 15-year latent period. No statistically significant increase in mortality from the cerebrovascular diseases in the combined cohort of the population exposed in the Southern Urals over a 65-year period received evidence. The obtained results are in good agreement with those received in the analysis of the effect in the Techa River Cohort in 2013. The latter covered a 53-year period (with minimum latent period of 15 years) and revealed statistically significant linear dose response for all diseases of the circulatory system (ERR/100 mGy – 0.036) and ischemic heart disease (ERR/100 mGy – 0.056).